2011
DOI: 10.1080/10538712.2011.593255
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Perceptions of Child Sexual Abuse Based on Perpetrator Age and Respondent Gender

Abstract: Child sexual abuse changes the lives of countless children. Child sexual abuse victims experience short and long term negative outcomes that affect their daily functioning. In this study, undergraduate students' perceptions of CSA were obtained using vignettes with an adult or child perpetrator and a general questionnaire. Results indicated participants receiving the child-on-child vignette were less likely to rate the vignette as abuse, saw the abuse as less severe, and assigned less blame to the perpetrator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…Consistent with other studies, all but three of the perpetrators in this sample were males (Giglio et al, 2011;Peter, 2009) and the average age of the perpetrators was 23.83 years with a range of 16 to 47 years (Carballo-Diéguez, Balan, Dolezal, & Mello, 2011;Cromer & Goldsmith, 2010;Giglio et al, 2011;Peter, 2009).…”
Section: Perpetrator's Characteristics Perpetrator's Gender and Agesupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with other studies, all but three of the perpetrators in this sample were males (Giglio et al, 2011;Peter, 2009) and the average age of the perpetrators was 23.83 years with a range of 16 to 47 years (Carballo-Diéguez, Balan, Dolezal, & Mello, 2011;Cromer & Goldsmith, 2010;Giglio et al, 2011;Peter, 2009).…”
Section: Perpetrator's Characteristics Perpetrator's Gender and Agesupporting
confidence: 90%
“…Also, the interview and the examination at the emergency department were done in a professional, careful, and gentle manner, reducing chances of "second victimization" (Learner, 2012). Furthermore, the low prevalence of self-injurious or violent thoughts observed in this study is consistent with other studies in which most of the child victims denied plans or desires to injure themselves or others-reactions that might be the result of less anxiety, and low self-blame (Coohey, 2010;Giglio, Wolfteich, Gabrenya, & Sohn, 2011). Other studies have reported different findings: McReynolds and Wasserman (2011) found that self-injury was twice as frequent among children who experienced sexual abuse than among those who had experienced other forms of maltreatment.…”
Section: Child Victim's Desires To Injure Self or Otherssupporting
confidence: 85%
“…However, older children are often perceived by jurors as more adult-like (Cossins, 2008), so allowing narratives that portray victims and defendants as having equal responsibility in the initiation and continuation of sexual encounters to become salient (Rodger et al, 2016). Further, jurors assume that the victim has more responsibility for their abuse if the defendant is also young (Reitz-Kruegr et al, 2016;Giglio et al, 2011) and…”
Section: Discussionmentioning
confidence: 99%
“…Laypersons assume greater responsibility for sexual activity on the part of the victim as the age difference between the two parties decreases (Reitz-Krueger, Warner, Newsham, & Reppucci, 2016), and if the defendants are also children, the abuse is viewed as less severe (Giglio, Wolfteich, Gabrenya, & Sohn, 2011), while alleged acts of sexual abuse by father figures are seen as more harmful (Reynolds & Birkimer, 2002). Guilty verdicts may thus be more likely when the age and power gaps between the two parties are larger (McCoy & Gray, 2007).…”
Section: Narrative Construction Is Dependent On Case Characteristicsmentioning
confidence: 99%
“…Parallel effects across perpetrators age (e.g., similarly-aged vs. much older offenders; cf. Giglio, Wolfteich, Gabrenya & Sohn, 2011) could also be investigated.…”
Section: Methodological Issues and Ideas For Future Researchmentioning
confidence: 99%